The 50 years of the Inter-American Human Rights System (My University, 2016)
Anniversaries, particularly those that reach important milestones, are good opportunities to reflect on achieved goals and present challenges. The year 2008 will mark sixty years since the adoption of the American Declaration of Rights and Duties of Man (Declaration) and it was 30 years ago that The American Convention on Human Rights (Convention) came into effect. In the year 2009, the Inter-American Commission for Human Rights (Commission or IACHR) will celebrate 50 years of existence, it will be the 40th. anniversary of the adoption of the Convention, and the 30th. of the installation of the Inter-American Court for Human Rights (Court). Without a doubt, these significant anniversaries invite reflection on the current situation of the Inter-American system for human rights and preparation necessary to confront the next five decades.